Response–reinforcer contiguity versus response‐rate–reinforcer‐rate covariance in rats' lever pressing: Support for a multiscale view. Issue 3 (25th March 2020) - Baum, William M.; Aparicio, Carlos F.
Abstract : The multiscale molar view sees behavior as a flow, like a river, extended in time. Matching theory expresses the way activities compete for time. Relative time taken by any activity depends on relative induction. The present experiment tested matching theory applied to concurrent contingent and noncontingent food. As adjunctive activities that compete with operant activity, we recorded hopper head entries and presses on a lever near the food hopper that had no programmed consequences. Eight naïve rats were first exposed to a variable‐time 60 s schedule, which across conditions was gradually transformed into a variable‐interval 60 s schedule by increasing the proportion of food that was delivered contingent on pressing a lever far from the hopper. Another group of 4 rats that had been trained to press a lever near a food hopper were introduced in the second condition, in which one food delivery was contingent on far‐lever pressing. We found induction following a power function to describe pressing on the far lever (operant activity). Matching theory combined with power‐function induction also accounted for adjunctive activity. Results with single contingent food deliveries provided little support for the molecular view that behavior consists of discrete responses "strengthened" by immediately following reinforcers.